Ballistic impact performance of Kevlar®/UHMWPE hybrid composite panels with a liquid thermoplastic resin, Elium® - Aswani Kumar Bandaru; Dinesh Kumar Kothandan; Hemant Chouhan; Hong Ma; Ronan M. O’Higgins (Materials & Design)
This study presents the ballistic impact performance of composite panels with novel liquid Methyl methacrylate (MMA) (Elium®) thermoplastic resin. The panels, which include Kevlar® (Kevlar) and ultra-high molecular weight polyethylene (UHMWPE), and hybrids with their combination (Kevlar/UHMWPE and UHMWPE/Kevlar), were manufactured with different numbers of layers (16 and 24) using vacuum-assisted resin transfer. These panels were tested against 0.38 lead round nose (300 ± 15 m/s) and 0.357 semi-jacketed soft point flat (550 ± 15 m/s) projectiles. The study assesses the ballistic impact performance of single fibre reinforced and the influence of hybridisation through various parameters such as, damage patterns, back face deformation, energy absorption, and residual velocity. The results reveal that 16 and 24 layer panels effectively defeated 0.38 projectile with relatively lower back face deformation while showing perforations for 0.357 projectile with varying residual velocities for different panel configurations. The hybrid combination of Kevlar/UHMWPE with Kevlar on the front demonstrated higher energy absorption with low residual velocity, leveraging the superior energy absorption capability of Kevlar and better stretching from UHMWPE. This study not only underscores the potential of Elium® resin-based composite panels for ballistic protection but also emphasises the crucial role of reinforcement hybridisation in enhancing the ballistic performance.